Exploring the Development and Existence of Islamic Education in the Netherlands - Rusdi, Rusdi (SYAMIL: Journal of Islamic Education, 2019)
Islamic education in the Netherlands has a rich and complex history that has evolved over the past several decades. The development of Islamic schools, mosques, and community centers has been a response to the growing need for education that reflects the Muslim identity of Dutch citizens. Despite challenges and controversies, the resilience of Islamic education in the Netherlands is a testament to its importance and relevance. This paper examines the evolution of Islamic education in the Netherlands, from its early beginnings to the present day. It explores the challenges faced by the Muslim community in establishing and maintaining Islamic schools, and how these schools have adapted to changing circumstances. The role of Islamic education in shaping the identities of Dutch Muslims is also explored, along with the impact of government policies on the development of Islamic education. Through a qualitative case study approach, this paper provides an in-depth analysis of the experiences and perspectives of key stakeholders in the field of Islamic education in the Netherlands. Findings suggest that Islamic education in the Netherlands is a dynamic and resilient field, with diverse perspectives and approaches that reflect the multicultural society in which it operates.Overall, this paper highlights the importance of understanding the evolution and resilience of Islamic education in the Netherlands, and its role in shaping the identities and experiences of Dutch Muslims. It also sheds light on the challenges and opportunities facing Islamic education in a multicultural and rapidly changing society.